English language teachers as a dissenter on a social networking site - Radzuwan, Ab Rashid; Normah, Yusof; Zanirah, Wahab (Australian International Academic Centre PTY LTD, 2016)
This paper explores how teachers discursively construct socially desirable identities to sustain their engagement in the Facebook Timeline community. Data were gathered from the Status updates and Comments on 29 Timelines belonged to Malaysian English language teachers who were purposively chosen as they often posted and commented on teaching related issues on their Timelines. The analysis shows that the commonest form of identity construction on the teachers’ Timelines was as a dissenter which had been carefully constructed to present positive self-images and cast blames on other people. The teachers questioned the expectations of the people around them, as they perceive that the expectations are unrealistic. This paper concludes that the teachers were being strategic in their postings where they provide justification for their views and ascribe particular identities to other people in the process of constructing their own identity as a dissenter.